Where is There? The Canadianization of the American Media Landscape - Weeks, Eric (International Journal of Canadian Studies / Revue internationale d’études canadiennes, 2009)
AbstractAn increasing number of American film and television productions are filmed inCanada. This paper argues that while the Canadianization of the American medialandscape may make financial sense, the trend actually causes harm to the culturallandscape of both countries. This study examines reasons contributing to thetendency to move production to Canada and how recent events have impactedHollywood's northern migration. Further, "authentic" representations of place onthe big and small screens are explored, as are the effects that economic runawayproductions—those films and television programs that relocate production due tolower costs found elsewhere—have on a national cultural identity and audiencereception, American and Canadian alike.